A 10 MW class data center with ultra-dense high-efficiency energy distribution: Design and economic evaluation of superconducting DC busbar networks. (1st July 2022) - Chen, Xiaoyuan; Jiang, Shan; Chen, Yu; Lei, Yi; Zhang, Donghui; Zhang, Mingshun; Gou, Huayu; Shen, Boyang
Abstract: With the rapid global developments of digital economy and internet-based technologies, the ultra-dense high-efficiency energy distribution and supply are becoming urgently essential for the data centers that contain large amounts of information-technology (IT) equipments. Considering the limitation of current-carrying capacity and huge ohmic loss of the conventional copper busbars, this paper presents a novel solution using high-temperature superconductor (HTS) DC busbars for data centers with the ultra-high current-carrying capacity and compact size. The full layouts of 3-grade HTS busbars are designed in accord with the industrial standards of date centers. The economic analysis on different busbar schemes for a 10 MW class data center is carried out. For the 100 V/100 kA scheme, the ratio of total operating cost (HTS busbars/copper busbars) can be down to 0.11. With the consideration of the power supply unit (PSU) conversion efficiency, the benefit-turnover period can be reduced from approximately 23 to 17 years. A general design guideline (technical design and economic analysis) is made for building HTS busbar networks in high-dense data centers. Overall, the novel design, technical evaluation and economic analysis of the superconducting DC busbar network can provide useful information and potential solutions for the future high-dense data centers. Highlights: High-temperature superconductor (HTS) busbars for high-power data centers. HTS busbars with ultra-high current-carrying capacity and compact size. Full layouts of 3-grade HTS busbars in accord with data center standards. Economic analysis on different busbar schemes for a 10 MW class data center. General design guideline of HTS busbar networks for high-dense data centers.